Temptation and Commitment in the Laboratory - Joachim Winter; Daniel Houser; Daniel Schunk; Erte Xiao (Verein für Socialpolitik, 2010)
Temptation and self-control in intertemporal choice environments are receiving increasing attention in the theoretical economics literature. Nevertheless, there remains a scarcity of empirical evidence from controlled environments informing behavior under repeated temptations. This is unfortunate in light of the fact that in many natural environments, the same temptation must be repeatedly resisted. This paper fills that gap by reporting data from a novel laboratory study of economic decisions under repeat temptations. Subjects are repeatedly offered an option with instantaneous benefit that also entails a substantial reduction to overall earnings. We show that this option is "tempting" in the sense that a substantial fraction of our subjects incur pecuniary costs to eliminate the choice, and thus commit to not choosing the tempting alternative. We compare the timing and price-elasticity of these commitment decisions to predictions from existing theoretical models of decision under temptation. Our data are broadly consistent with theory, with the notable exception that commitment often occurs with delay rather than at the first opportunity. Moreover, the timing of commitment is significantly impacted by the cost of the commitment device. The patterns we report have direct implications for economic theory, and are a first step toward designing mechanisms that promote prudent economic decisions under temptation.
Keywords: C91; D11; C90; 330; self-control; willpower; temptation; commitment; laboratory experiment